Synthesis and Spectral Studies of Novel Palladium (O) Complex with Ciprofloxacin Antibiotic - S. Majeed, N.; K. Kareem, I.; N.A. Jafar, N. (International Journal of Engineering and Technology, 2018)
New complex of Palladium (0) with ciprofloxacin has been synthesized, The complex was portrayed by different physico - substance systems like essential examination, m.pt. , TLC, molar conductance estimation, attractive helplessness,13C- NMR, 1H-NMR and FT-IR. According to the results obtained, tetrahedral structure suggested for the prepared complex. The neutral ligand act in a Didentate mode, binding through oxygen atom of carbonyl group in pyridonering and oxygen atom of carboxyl ate group.Â Â